Interpretation of Freedom of Expression in Public from the Perspective of Law, Democracy, and Human Rights - M. Jasuli Ramadhan; Hajairin; Ridwan (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2025)
Freedom of expression in public is a constitutional right and a fundamental right that occupies a central position in the building of a democratic rule of law. However, its implementation in Indonesia is still marked by tension between normative guarantees and widespread restrictive practices, especially since the public sphere shifted to the digital realm. This article aims to reinterpret the meaning of freedom of expression in public by weaving together three perspectives simultaneously: positive law, substantive democratic theory, and international human rights principles, an interdisciplinary approach rarely integrated in previous studies that tended to be partial to only one domain. This research uses a normative juridical method with a legislative approach, a conceptual approach, and a comparative approach to international human rights norms, supported by an examination of the latest Constitutional Court decisions and the policies of the National Human Rights Commission. The results of the study indicate that the Indonesian legal framework, starting from Article 28E paragraph (3) of the 1945 Constitution to Law Number 9 of 1998, has provided adequate textual guarantees, but the interpretation of the phrase limitation in various derivative regulations, especially the Electronic Information and Transactions Law, is still elastic and has the potential to be misused to silence legitimate criticism. The novelty of this research lies in the construction of a three-layer analytical framework, namely the constitutional layer, the deliberative democracy layer, and the international human rights limitation clause layer, which are used simultaneously to assess the legitimacy of each form of restriction on freedom of expression, in contrast to previous research which generally only highlights the criminal aspect or the human rights aspect separately. This article recommends a more precise reformulation of the norm of limitation, strengthening independent oversight of law enforcement in the digital space, and internalizing the Siracusa proportionality principle into Indonesian judicial practice as a strategic step to strengthen the consolidation of substantive democracy.